The Legacy of Adolph Reed, Jr.'s "Black Urban Regime". (September 2016) - Bennett, Larry
Adolph Reed's extended essay, "The Black Urban Regime: Structural Origins and Constraints, " was a provocative and insightful examination of the first generation of African-American municipal officials in major American cities. The criteria articulated by Reed in assessing the policy record of that group of black mayors, council-members, and leading administrators have retained their applicability in the face of contemporary efforts to shape and execute progressive local policy.